ANALYSIS OF WEEKLY INTERNAL AND EXTERNAL LOAD FLUCTUATION IN PROFESSIONAL BASKETBALL (Kinesiology, 2025)
The present work analyzes the weekly load fluctuation, internal and external, throughout a season in a professional basketball team. To analyze the internal load factor, the session Rate of Perceived Exertion (sRPE) has been used, and the Integral Analysis System of Training Tasks (SIATE) has been used to monitor the external load. This is the first work that analyzes the complementary use of these two low-cost load monitoring tools. Firstly, the scores distribution obtained in both tests has been characterized. Secondly, an important and positive correlation was found since the association between the scores in sRPE and SIATE shows to increase together. Finally, we compared the scores of the study groups corresponding to the weeks without match (0-g), with one match (1-g) and with two matches (2-g) in each of the variables. Regarding sRPE, differences have been found between 0-g and 2-g, and between 1-g and 2-g. Furthermore, we observed differences in SIATE between 0-g and 1-g, 1-g and 2-g, and between 0-g and 2-g. Taken altogether, our study suggests that the complementary use of sRPE and SIATE is an effective and methodical monitoring training system.Key words: session Rate of Perceived Exertion, Integral Analysis System of Training Tasks, internal load, external load, weekly load fluctuation